If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(7-x)-(x+2)=5+7(x-9)
We move all terms to the left:
3(7-x)-(x+2)-(5+7(x-9))=0
We add all the numbers together, and all the variables
3(-1x+7)-(x+2)-(5+7(x-9))=0
We multiply parentheses
-3x-(x+2)-(5+7(x-9))+21=0
We get rid of parentheses
-3x-x-(5+7(x-9))-2+21=0
We calculate terms in parentheses: -(5+7(x-9)), so:We add all the numbers together, and all the variables
5+7(x-9)
determiningTheFunctionDomain 7(x-9)+5
We multiply parentheses
7x-63+5
We add all the numbers together, and all the variables
7x-58
Back to the equation:
-(7x-58)
-4x-(7x-58)+19=0
We get rid of parentheses
-4x-7x+58+19=0
We add all the numbers together, and all the variables
-11x+77=0
We move all terms containing x to the left, all other terms to the right
-11x=-77
x=-77/-11
x=+7
| 3n-1=1/8 | | 21x/4-4/3=76 | | 5k−2=7 | | 2/3x+5/7=11/5(x+2) | | 5(z+6)=4(z-8)+z | | 27x+5=23.4x-1 | | 75+20x=35 | | 3x–1=6+2x | | 3m^2-2m+12=0 | | 24x-48÷6=4 | | 5x=11(2x-3)÷2 | | p+3=7-9p | | 12x2+24=0 | | 3x+1=11=2x | | 1/3(9x-12)-6x+15=-19 | | 95x=35x | | 5x=11(2x-3÷2) | | 7(5x-4)=3(8-5x) | | 8m-4=3+8 | | 5x-14+3x+2+x+32=180 | | 8w-8=4w-7 | | 90+5.45x=13.63x | | 4x-6+2x=2(3x-30 | | 5x=11(2x-3/2 | | 2x+6X+3X+8X+4=338 | | -4x+4/3=20 | | x+4X+X-20=180 | | (2y-12)=90 | | (X+2)+(2x+2)=4x+1x+2 | | 27x+5=-x+9.8 | | 20+9x=180 | | x=5=-5x+5 |